Barriers and strategies for building information modelling implementation: a comparative study between New Zealand and China - Ma L; Lovreglio R; Yi W; Yiu TW; Shan M (Massey University)
Building Information Modelling (BIM) is a sharing platform that can present a parametric 3 D model with various project information in the form of a digital display. In recent years, BIM adoption has become increasing globally as the Architectural, Engineering, Construction (AEC) industry has recognised its benefits. Meanwhile, many challenges of BIM adoption in different countries have been well documented. To address the gap in literature, this study examines the differences and similarities of BIM adoption between New Zealand and China. A questionnaire was conducted across the two countries to investigate the barriers and strategies for the implementation of BIM. Data from 146 respondents was collected in New Zealand and China. The result shows that there is a difference in the perception of Knowledge Barrier, Technology Barrier, Internal Strategy and External Strategy (Legal/Technology viewpoint) between New Zealand professionals and Chinese professionals. The differences identified offer important implications for government agencies to promote BIM implementation and for BIM service providers to better target the end-users.
Keywords: 0905 Civil Engineering; 1202 Building; 1504 Commercial Services